Analysis of Vegetation Trend in Mazandaran Province with an Emphasis on Land Use Changes Using MODIS NDVI Time Series - Morteza Dastigerdi; Mehdi Nadi; Bahareh Shamgani Mashhadi; Mohaddeseh Hatamipour; Omid Mahdavi amrei (پژوهشنامه مدیریت حوزه آبخیز)
Extended Abstract Background: Vegetation is one of the main components of biosphere preservation that acts as a link between soil, water, and atmosphere. It is crucial in providing organic matter, regulating the carbon cycle, and exchanging energy on the surface of the earth. In recent years, climate change and global warming have caused frequent events, such as floods, heat waves, and droughts, which can damage terrestrial ecosystems. Climate change directly affects the growth of vegetation; on the other hand, changes in vegetation cover give feedback to climate change by regulating water, energy exchange, and carbon dioxide concentration. Methods: The research was carried out in Mazandaran province to analyze vegetation trend in the study area during the 2001-2020 period. The 16-day composite MODIS-NDVI time series data, named MOD13Q1, with a spatial resolution of 250 meters (920 NDVI images) were used for this purpose. The non-parametric Mann-Kendall method was employed to investigate changes in vegetation activity and trend significance. The overlying vegetation trend map and the location of big cities and main roads of the province were also investigated in this research. Results: A decreasing trend of vegetation cover was observed in 16% of the total studied area, and the rest showed an increasing trend, although the significant decrease and increase of vegetation cover occurred in 5% and 65% of the area, respectively, with a 95% confidence level. The vegetation trend map showed that the most significant reduction of vegetation in the last 20 years occurred in coastal areas and low-altitude regions, especially around big cities and main roads entering the province. Decreased vegetation around the metropolises is expected due to the increase in population and the need for urban development. However, the results showed that the most significant decrease in vegetation occurred in the cities of Mahmudabad (19%), Babolsar (17%), Ghaemshahr (10%), and Jouybar (9%). Unlike the big cities of Sari and Ghaemshahr, the cities of Sorkhrood, Mahmudabad, and Babolsar are at the top of the cities with reductions in vegetation cover in the last 20 years. Unfortunately, this is not due to urban development and increasing population, but drastic changes in the use of agricultural land and citrus orchards and turning them into private villas are the main factor in the reduction of vegetation. Comparing the vegetation trend map with the main roads of the province reveals that a significant reduction of vegetation has occurred around the main roads entering Mazandaran province, especially on the Haraz, Firouzkouh, and Farim roads. In contrast, smaller areas of vegetation cover reduction were observed around the Chalus road. The investigation of the areas with positive vegetation cover trends showed that the highlands of the province, especially the eastern highlands, experienced a significant increase in vegetation cover. However, a less significant positive trend of vegetation was observed in the western highlands. Rather, most of these areas have experienced no trend conditions in the past 20 years, which could be due to the recent global warming and the higher temperature in the east of the province than in the western regions, which generally has caused suitable temperature conditions for the growth of vegetation in the eastern highlands of the province. It seems that the western highlands still do not have suitable temperature conditions for the growth of vegetation. Conclusion: The results of this research show that the changes in vegetation in Mazandaran province are under the control of two natural and human factors, and the former (climate) has caused an increase in vegetation in 65% of the area of the province, especially in the highlands, probably caused by the increase in temperature. The recent global warming has made it possible to provide living conditions for plants in the highlands of the province, especially the eastern highlands. Nevertheless, the human factor has been destroying vegetation throughout the province, especially in tourist areas and those with easy access. As such, a significant trend of vegetation reduction was observed both on the coasts, around metropolises, in the heart of the Hyrkan forests, and in the heights near the main roads. A significant decrease in vegetation cover has occurred in 5% of the area of the province, and these decreases were observed mostly in the plains, coastal strip, low altitudes with low slopes, outskirts of cities, and roads of the studied area. Vegetation is also being destroyed in the marginal areas of the roads from Ramsar to the neighboring western province, Gorgan Sari, Tehran, Chalus, Haraz, and Firuzkouh, which can be the main reason for the increase in traffic load, changes in land use, and the construction of recreational facilities and villas. Based on the results of this research, extreme changes in land use in the last 20 years are very evident, and if the human process of land use change continues along with the loss of water and soil resources, we may see irreparable blows to the ecosystem of the Caspian systems in the near future.